Elaboración de queso fresco mediante la utilización de tres niveles de cuajo de origen vegetal de la papaya nacional (Carica Papaya) con diferentes concentraciones de latex en salmuera en Santo Domingo. - Quito Betancourt, Fanny Mirian (2011)
This investigation was made in the “Calazacön” higher Technologycal Agricultural Institute which is located in Santo Domingo city, Santo Domindo de los Tsáchilas Province, in the Aurora sector 61/2 Km. in Quevedo avenue left border. Geografically it is located at 557 m.s.n.m., 00º14,0`south latitude and 79º and 12,0º west longitude. This experiment was made in two months from February to March. The main objetive of this investigation was to elaborate a fresh cheese using three levels of curd and it has vegetable origen and comes from the national papaya with different concentrations of latex in the brine. A factorial experiment was planted 2x3+2 y alloy full desing and the treatments resulted from de combination of latex in brine with 3 porcentages of coagulation: T1: chesse with commercial curd (testimony 1): T2: Concentration of latex in brine with a relation 1:1 with a percentage of coagulation of 1:25, T3: Concentration of latex in brine with a relation 1:1 with a percentage of coagulation of 1,50; T4, Concentration of latex in brine with a relation 1:1 with a percentage of coagulation 1,75; T5: chesse with commercial curd (testimony 2): T6: Concentration of latex in brine with a relation 1,33:1 with a percentage of coagulation of 1:25, T7: Concentration of latex in brine with a relation 1,33:1 with a percentage of coagulation of 1,50; T8, Concentration of latex in brine with a relation 1,33:1 with a percentage of coagulation 1,75. To do this step of the investigation we proceded to make at starting the collection of the matter, after the reception, filtration, pasteurization, cooler, increasing calcium chloride, premature, coagulate, coagulate cut, the first shake, repose, first unserum, washed, second shake, second unserum, molding first, second and third turn, sheated and stored. The organoléptica evaluation was made to 10 people from the Agricultural institute with the objective to determine what treatment had more acceptance by the consumers in flavor, color and texture. Besides here were determined the output in every treatments, getting the higher the T2, the average results were submitted to the lest o meaning of Tukey al 5%. As conclusion it expressed that the concentration of latex in brine to (1:1) combined with 1,25% of coagulation (T2) gave the best results in physical and chemical characteristics (protein, humidity, oil, ash) output and organoleptica (color, flavor, texture), besides it got the greater benefit-cost ($ 1,06).